The Entrepreneurial Self Fabricating a New Type of Subject - Bröckling, Ulrich 1959- (SAGE Publications, 2015)
A seminal study from a major name in sociology. Ulrich Brockling explores how the contemporary call for entrepreneurship leads to permanent 'over-challenging', exacerbates feelings of powerlessness and generates unbounded anger. We are promised that the most capable will reap the most success, but no amount of effort can remove the risk of failure